THE INFLUENCE OF PARENTS' ROLE ON STUDENTS’ LEARNING ACHIEVEMENT AT SMA NEGERI 1 LAWA - Meri Yati (Educouns Journal: Jurnal Pendidikan dan Bimbingan Konseling, 2023)
This study aims to determine the effect of the role of parents on student achievement at SMA Negeri 1 Lawa in the 2020/2021 school year. This research was conducted using quantitative methods, by taking samples by simple random sampling of 65 students of SMA Negeri 1 Lawa in the academic year 2020/2021. Data were collected through a questionnaire with a Likert scale. The data analysis technique used simple linear regression analysis with the help of a computer program SPSS 23 for windows. The results showed that there was an effect of the school social environment on student learning motivation. The regression equation Y = 25.078 - 0.685 X with the quantitative increment of the two variables was 1: 0.685, this comparison shows that if there is an increase of one time / unit in the role of parents variable ( X) then there will be a decrease of 0.685 in the student achievement variable (Y). The regression equation is significant or will not be tested using the Fcount value at the significant level of 0.05. Means Ha accepted and Ho rejected. The conclusion is that the hypothesis that there is an effect of the role of parents on student achievement at SMA Negeri 1 Lawa is accepted and significant, this is indicated by the value of the regression coefficient (F) of 44,590 with a significant 0.002.